Development of Sites Google Learning Media to Improve Student Learning Comprehension - Nessa Nabila Nessa; Meini Sondang Sumbawati (Program Doktor Pendidikan FKIP Universitas Lampung, 2026)
Objective: This study aimed to develop Google Sites-based learning media for Basic Electronics Engineering, focusing on active and passive components, and to evaluate their feasibility and impact on student comprehension. The research was guided by three questions: (1) How is the media developed? (2) How feasible is it? (3) Does it improve comprehension?Method: The Research and Development (R&D) approach utilized the 4D model (Define, Design, Develop, Disseminate), with dissemination limited to a field trial. Three experts, including two lecturers and one vocational teacher, validated the media, materials, and test items using a 1–4 Likert scale. The media was implemented with 34 Grade X students from SMK Negeri 1 Jetis, Mojokerto. Student comprehension was assessed using a validated 20-item multiple-choice pretest and post-test. Results: The developed media, named El-Learn, was highly feasible (mean validation score = 3.80/4.00 or 95%). Student comprehension improved significantly from a pretest mean of 53.00 to 86.53 (N=34), with an N-Gain of 0.69, showing moderate improvement and approaching the high threshold of 0.70. Conclusion: The Google Sites-based learning media was highly feasible and enhanced comprehension of abstract electronics concepts in vocational education. Limitations of the study include the use of a one-group pretest-posttest design and implementation at a single school. Future research should incorporate control groups, larger sample sizes, and additional vocational subjects.